FUNDAMENTALS OF DIGITAL SIGNAL PROCESSING - SCHILLING ROBERT J; HARRIS SANDRA L (DELHI, 2005)
DSP
UNDER TEQIP PHASE -II
Electronics & communications
ECE
Keywords: COMMUNICATION; DIGITAL SIGNAL PROCESSING